Comparison of prophylactic versus regular use of antibiotics in caesarean section - Jirange, Umesh Maruti; Sneha, Y.; Mallika, P. P. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Surgical site wound infections and associated complications after caesarean delivery are important causes of maternal morbidity, increased duration of hospital stay and cost of treatment. Prophylactic antibiotic usage decreases the risk of these wound infections. Because of variations in patient profiles and a lack of knowledge regarding asepsis, clinicians are reluctant to implement the recommended single-dose preoperative antibiotic prophylaxis. Methods: This was a prospective study involving 200 women undergoing caesarean delivery at obstetrics and gynecology department of MNR Medical College and Hospital, Fasalwadi, Sangareddy, tertiary care centre. Eligible participants were divided into two groups. Group A received single dose antibiotic prophylaxis of ceftriaxone 1 gm intravenously 30-40 minutes before caesarean section and group B received cefotaxime 1 gm +sulbactam 500 mg 30-40 minutes before the caesarean, followed by cefotaxime+sulbactam and ornidazole intravenously for the first 3 post-operative days followed by oral cefixime for the next 5 days. Postoperatively, both groups of patients were followed up for febrile morbidity, UTI, wound infection, vaginal infection. These parameters were compared across the two groups. Results: There were 100 patients in each group. Baseline characteristics, indications for caesarean delivery, operative duration and difficulties were similar. Post-operative morbidities like fever did differ significantly, UTI, wound infection, vaginal infection did not differ significantly. Few of the women needed prolongation of hospital stay. Conclusions: Preoperative prophylactic antibiotic regimen was as effective as regular antibiotic regimen prophylaxis for routine caesarean delivery. Judicious use of limited antibiotics should be encouraged to decrease antibiotic resistance, with the added benefit of being economical.